LEARNING LOSS DAN FAKTOR-FAKTOR PENYEBAB DI SEKOLAH MENENGAH PERTAMA (SMP) - Riski Sovayunanto (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
Distance learning in North Kalimantan has been going on for one year, this is one of the impacts of the spread of covid-19. Prolonged school closures are feared to lead to decreased student learning competence and lead to learning loss, which is a condition where students lose knowledge, abilities and skills. The purpose of this research was to determine how many junior high school students in North Kalimantan were at risk of learning loss. The importance of this research is to be the basis of decision making to overcome learning loss in North Kalimantan. The Research method used quantitative descriptive approach. The research sample consisted of 610 junior high school students, where the sampling techniques used cluster sampling. The results of the study found a total of 111 students in North Kalimantan identified learning loss, then as many as 408 students were at great risk of experiencing learning loss. The remaining 91 students did not experience learning loss.